1995
DOI: 10.1016/0767-399x(96)80101-5
|View full text |Cite
|
Sign up to set email alerts
|

Case management: a critical review of the outcome literature

Abstract: Case management has been an integral part of psychiatric practice in the United States for over a decade and has generated a large body of literature. The application of case management principles to the care of people suffering from psychiatric disorders is becoming increasingly popular in the United Kingdom and Europe and literature is now beginning to be published. However, no definitive statements about the efficacy of case management have been made due to a range of conceptual and methodological problems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 39 publications
1
42
0
1
Order By: Relevance
“…Although we found large improvements in global psychiatric functioning and some reduction in cannabis use for the TLC group, we observed little improvement on the subscales of the BASIS-32 or reductions in alcohol and cocaine use. This is consistent with the conclusions of Holloway et al 24 , who reported that of the case management studies they reviewed a majority failed to find statistically significant improvements in symptomatology. Though it is possible that our relatively small sample size limited the statistical power of the study, it is also plausible that six months is an insufficient period of time in which to expect psychiatric and substance abuse problems to stabilize in dually diagnosed subjects.…”
Section: A Brief Community Linkage Intervention 149supporting
confidence: 81%
“…Although we found large improvements in global psychiatric functioning and some reduction in cannabis use for the TLC group, we observed little improvement on the subscales of the BASIS-32 or reductions in alcohol and cocaine use. This is consistent with the conclusions of Holloway et al 24 , who reported that of the case management studies they reviewed a majority failed to find statistically significant improvements in symptomatology. Though it is possible that our relatively small sample size limited the statistical power of the study, it is also plausible that six months is an insufficient period of time in which to expect psychiatric and substance abuse problems to stabilize in dually diagnosed subjects.…”
Section: A Brief Community Linkage Intervention 149supporting
confidence: 81%
“…82 The use of hospitalisation as an outcome measure has been criticised as inadequate for assessing programme success in this population, given that rates of hospital admission and length of inpatient stay can be influenced by other factors, such as local service configuration and bed availability. 84 Such uncertainty and variability raise crucial questions regarding the use and effectiveness of the CPA in practice, especially where researchers attempt to make judgements on programme outcome or cause-effect comparisons across more than one research site. The lack of clarity regarding the exact nature of the CPA in practice reflects a similar vagueness globally about the concept of care co-ordination.…”
Section: Meta-narrative Reviewmentioning
confidence: 99%
“…Les études sur le modèle ACT en comparaison avec un autre, ont été exclues. D'autres articles ont été identifiés à partir de listes de références des synthèses répertoriées (Holloway et al, 1995 ;Scott et Dixon, 1995 ;Baronet et Gerber, 1998 ;Marshall et al, 1998 ;Mueser et al, 1998 ;Ziguras et Stuart, 2000 ;Aubry et al, 2004 ;Corrigan et al, 2008 ;Dieterich et al, 2011). Ce processus initial a permis d'identifier 89 études (dont plusieurs sont rapportées en plusieurs articles).…”
Section: Méthodesunclassified